MEMPOSISIKAN MANUSIA SEBAGAI TITIK SENTRAL DALAM BERHUKUM - M. Muslih M. Muslih (Jurnal LEX SPECIALIS, 2012)
Abstract Indonesia as a country that was once colonized by the Dutch in the period of time, then in the